PENGEMASAN DAN PELABELAN PRODUK TURUNAN JAMUR TIRAM BERUPA KALDU DI DESA GIRI MUKTI KABUPATEN PENAJAM PASER UTARA - Hendriyani, Irna; Johnson, Ricky; Perdana, Muhammad Aris; Aprillia, Metta; Yulhim, Ananda; Tasyaf, Andi Audila Amanda; Ixcal, Alex Chairrul; Pratama, Ezy Nizam; Wiwoho, Rangga Satrio; Putra, Calvin Pratama (Nindikayla Institute, 2023)
Giri Mukti Village is a village located in Penajam, North Penajam Paser district, East Kalimantan province. Giri Mukti Village has potential, one that stands out and can be empowered easily in Giri Mukti Village is oyster mushroom cultivation. In order to increase the economics of a product, these oyster mushrooms can be made into processed products such as broth so that they have a higher selling price and are more salable in the market. In order to maintain the quality of the oyster mushroom broth so that it can survive, a container is needed as packaging and labeling on the package containing the name of the product and the ingredients for any composition used in the oyster mushroom broth